2006
DOI: 10.5194/angeo-24-1969-2006
|View full text |Cite
|
Sign up to set email alerts
|

Satellite observations of lightning-induced hard X-ray flux enhancements in the conjugate region

Abstract: Abstract. Preliminary examination of October-December 2002 SONG (SOlar Neutron and Gamma rays) data aboard the Russian CORONAS-F (Complex Orbital Near-Earth Observations of the Activity of the Sun) low-altitude satellite has revealed many X-ray enhanced emissions (30–500 keV) in the slot region (L ~ 2–3) between the Earth's radiation belts. In one case, CORONAS-F data were analyzed when the intense hard X-ray emissions were seen westward of the South Atlantic Anomaly in a rather wide L shell range from 1.7 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The reason for precipitation is violation of the stable motion of the trapped particles, which may be caused by magnetic storms ), lightning discharges (e.g., Voss et al 1984Voss et al , 1998Bučík et al 2006), earthquakes (Galper et al 1995;Aleksandrin et al 2003) or the man-made VLF transmitters on the ground. Schematically, processes leading to precipitation are as follows.…”
Section: Radiation Belt Electronsmentioning
confidence: 99%
“…The reason for precipitation is violation of the stable motion of the trapped particles, which may be caused by magnetic storms ), lightning discharges (e.g., Voss et al 1984Voss et al , 1998Bučík et al 2006), earthquakes (Galper et al 1995;Aleksandrin et al 2003) or the man-made VLF transmitters on the ground. Schematically, processes leading to precipitation are as follows.…”
Section: Radiation Belt Electronsmentioning
confidence: 99%
“…Short pulses of γ rays of duration less than about 1 ms with hard energy spectra consistent with bremsstrahlung and related to atmospheric electrical discharges have been first reported by Fishman et al (1994) using data from the BATSE instrument on board of CGRO satellite. Until now there is rather long list of literature on TGF as well as on physical interpretation and on suggestions/plans for future missions (e.g., Bučík et al, 2006;Connaughton et al, 2013;Cummer et al, 2014;Dwyer, 2008;Dwyer et al, 2012;Dwyer & Uman, 2014;Kudela & Błecki, 2015;Lefeuvre et al, 2008;Østgaard et al, 2008;Smith et al, 2005;Hare et al, 2016, and references within those papers).…”
Section: Introductionmentioning
confidence: 99%
“…In this region, the resonance cavities are excited by neutral winds [ Surkov et al , ], where substantial OD [ Thomas and Melott , ] and large quantities of NO + (altitudes of 110–140 km) exist [ Dobbin et al , ]. However, according to Feldman et al [], X‐ray radiation is found in the area at ± 43.3 ° geographic latitude (GLAT), which was reconfirmed later in the conjugated region [ Bučik et al , ]. The gamma spectrum is similar to the data observed at middle and high latitudes [ Akyüz et al , ].…”
Section: Resultsmentioning
confidence: 61%